Two Point Correlation Functions for a Periodic Box-Ball System - Mada, J.; Tokihiro, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
We investigate correlation functions in a periodic box-ball system. For the second and the third nearest neighbor correlation functions, we give explicit formulae obtained by combinatorial methods. A recursion formula for a specific N-point functions is also presented.